PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIVE LEARNING TIPE NHT DIKELAS VIII SEMESTER I T.A 2022/2023 DI SMPN 3 TILATANG KAMANG - Nur Aini Fitri; Aniswita Aniswita; Maikartini Maikartini (KOLONI, 2022)
Students achieve KKM on mathematics learning outcomes. That is, in Cycle 1, there were 9 students who reached 70 or more, and in Cycle 2, up to 13 students reached 70. Based on the learning conducted at SMPN 3 Tilatang Kamang, class VIII's mathematics learning achievement is still low. This is because the teacher does not use group learning. The motive of this study was to discover whether or not the software of the "Numbered Heads Together" cooperative learning model can improve students' mathematics learning outcomes. The investigative method used is the PTK method at SMPN 3 Tilatang Kamang. This classroom action research method has two cycles, each consisting of planning, implementing, observing, and reflecting. This classroom action research was carried out at SMPN 3 Tiratan Kaman in semester I of the 2022-2023 school year with a total of 20 students in class VIII subjects. This study found that in Cycle I, 9 students (45%) achieved KKM scores above 70, and in Cycle II, 13 students (65%) achieved scores above 70. The KKM achieved being 70, it can be concluded that learning using cooperative learning models of the "number heads together" type can improve student learning outcomes in mathematics. Keywords: studying consequences; cooperative learning; numbered heads together.